Visualización de datos de movimientos telúricos utilizando web Scraping y social Network Analysis - Moreira García, Francisco Simón (2022)
Although telluric movements are unpredictable, it is possible to analyze their characteristics. To analyze these events, data sets collected by seismic sensors are studied and published on official seismology web pages. Due to the frequency of these events, there is a need to report on earthquakes in different regions of the world. However, the media, such as newscasts and newspapers, emphasize the earthquake movements with the greatest magnitude, without considering that there are other characteristics that are useful to determine the level of damage that can be caused by an earthquake. On the other hand, official web pages publish telluric records in tabular form and do not process the data to generate reports, which makes analysis difficult due to the number of events that occur daily in different regions of the world.